RESPONSE OF NORMAL FAULTS TO GLACIAL-INTERGLACIAL FLUCTUATIONS OF ICE AND WATER MASSES ON EARTH'S SURFACE - Hampel A.; Hetzel R. (My University, 2006)
Changes in surface loads during glacial-interglacial cycles and the associated flexure and rebound of the lithosphere alter the stress field in actively extending regions and may lead to slip rate variations on normal faults. In particular, loading may cause a period of seismic quiescence that is followed by temporal clustering of earthquakes during and after unloading. Here we present a suite of finite element experiments to evaluate how the magnitude, distribution, and temporal evolution of the load, as well as rheological parameters of the lithosphere and asthenosphere, influence the response of a normal fault. The results show that the duration of the seismically quiet period during loading and the intensity of the slip rate increase during unloading are primarily controlled by the magnitude of the load. The time lag between the changes in loading and the reaction of the fault is mainly determined by the viscosity of the asthenosphere. Parameters that play only a minor role for the fault's response include the rate of load removal, fault strength, and the thickness of the lithosphere. Our results imply that earthquake recurrence models derived from Holocene slip histories may not be representative for the long-term evolution of seismogenic faults. Copyright 2006 by the American Geophysical Union.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен